PENERAPAN ECOLITERACY DALAM MENINGKATKAN PERILAKU RAMAH LINGKUNGAN SISWA DI SEKOLAH DASAR - Nugroho, Bayu Sapto; Sumardjoko, Bambang; Desstya, Anatri; Rahmawati, Laili Etika; Widyasari, Choiriyah (Universitas Veteran Bangun Nusantara, 2025)
The implementation of ecoliteracy in elementary schools is an important strategy in shaping students' green behavior from an early age as part of character education and ecological awareness. This study aims to describe the application of ecoliteracy in improving students' green behavior at SD Negeri Gumpang 01, a school that has won the Adiwiyata School award at the Central Java Province level. The method used was descriptive qualitative research with a naturalistic approach, involving the principal, teachers, and students as research subjects. Data collection was conducted through in-depth interviews, observation, and documentation, with interactive analysis techniques and triangulation of sources and methods to ensure data validity. The results showed that the implementation of ecoliteracy was carried out through integration in the local wisdom-based curriculum, project-based learning, extracurricular activities, collaboration with parents and communities, and utilization of media and technology. This strategy clearly encourages increased student self-awareness, changes in attitudes and habits, and a growing sense of social responsibility for the environment. The implementation of ecoliteracy not only increases students' understanding of the importance of protecting the ecosystem, but also internalizes ecological values into daily life. Thus, learning integrated with environmental values can form a sustainable school culture. The implementation of ecoliteracy not only improves students' understanding of the importance of maintaining the ecosystem, but also internalizes ecological values into daily life. Thus, learning integrated with environmental values can form a sustainable school culture and strengthen the character of environmental care in elementary school students.